Pengaruh Model Kooperatif Tipe Think Talk Write Berbantuan Video Animasi Terhadap Hasil Belajar Siswa Kelas V Tema 8 Di SDN 060874 Medan - Lisna Juniani Situmorang (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to determine the effect of the Think Talk Write type cooperative model assisted by animated videos on the learning outcomes of fifth grade students of theme 8 of our best friend's environment, sub-theme Humans and the Environment at SDN 060874 Medan. This research uses a type of quantitative research that uses experimental methods with a nonequivalent control group design. The population of this study were all fifth grade students of SDN 060874 Medan. The samples of this study were class V-A and V-B with Class A as the experimental class and class V-B as the control class. The results of this study indicate that there is an effect of learning by using a cooperative model of think talk write type assisted by animated videos on the learning outcomes of grade V theme 8 students at SDN 060874 Medan.